Brexit and its consequences on EU defense policy and security - Štětkář, Matěj (2017)
This thesis discusses the current issue of Brexit in the light of future EU defense policy and security from the economic and political point of view. When the results of then British referendum were announced, it was a shock to many. The question that came together with this outcome and the current security threats in the world was whether the UK and the EU alone can handle this new situation. The UK, as one of the biggest military spenders in the world, could be a loss for the EU if they decided not to continue with their cooperation. This goes also vice versa. The purpose of this thesis was to discuss whether we should expect a significant change after Brexit in the policies of the European defense and security through brief analysis of the budget of the EU and the military expenditures of UK and other significant members. In this thesis I have outlined the budget of the EU and its significance in the future of the European defense and security together with current security issues of the European Union. Last but not least, based on my research, I have suggested a possible scenarios that might follow British exit from the EU. Statistical data are mainly taken from Eurostat and nonstatistical from a number of research papers already published on this topic. The issue of Brexit and defense policy and security will be still very discussed topic in the next few years with a number of possible outcomes, but UK will be always geographically part of Europe and so their relationship with the EU will be always very close.